Location of the radial nerve along the humeral shaft between the prone and lateral decubitus positions at different elbow positions - Sitthiphong Suwannaphisit (Nature Portfolio, 2021)
Abstract Identification of the radial nerve is important during the posterior approach to a humerus fracture. During this procedure, the patient can be placed in the prone or lateral decubitus position depending on the surgeon’s preference. The distance from the radial nerve to the osseous structures will be different in each position. The purpose of this study was to identify the safety zones in various patient and elbow flexion positions. The distances from the olecranon to the center of the radial groove and intermuscular septum and lateral epicondyle to the lateral intermuscular septum were measured using a digital Vernier caliper. The measurements were performed with cadavers in the lateral decubitus and prone positions at different elbow flexion angles. The distance from where the radial nerve crossed the posterior aspect of the humerus measured from the upper part of the olecranon to the center of the radial nerve in both positions at different elbow flexion angles varied from a mean maximum distance of 130.00 mm with the elbow in full extension in the prone position to a minimum distance of 121.01 mm with the elbow in flexion at 120° in the lateral decubitus position. The mean distance of the radial nerve from the upper olecranon to the lateral intermuscular septum varied from 107.13 to 102.22 mm. The distance from the lateral epicondyle to the lateral edge of the radial nerve varied from 119.92 to 125.38 mm. There was not significant contrast in the position of the radial nerve with osseous landmarks concerning different degrees of flexion, except for 120°, which is not significant, as this flexion angle is rarely used.